Talk it: Tutorial support and mental health in higher education students - Quiroz Fragoso, Jennifer (European Public & Social Innovation Review, 2024)
Introduction: in this article stated that it was born within the framework of the research project where the campaign generated: “Háblalo” for its purposes, as part of the mental health care of the students of the Metropolitan Polytechnic University of Hidalgo. from 2019 to 2023. The methodology used was a longitudinal study with an eight-career program generation cohort that was developed over four years. As a discussion, part of the campaign, all university staff were instructed to be able to listen to students with their various problems, under the assumption that active listening as first psychological help can prevent risky behaviors and attitudes. As a result, the study has shown that listening as a first attention involves providing practical and non-invasive help, in addition to knowing the needs and concerns of the student. Furthermore, its conclusions allow us to visualize new lines of research around tutoring and mental health, as well as the tutoring function as a first psychological help with active listening as a prevention and action tool.